2022
DOI: 10.24235/ileal.v7i2.10208
|View full text |Cite
|
Sign up to set email alerts
|

Minat Baca Siswa SMP: Faktor Latar Belakang Ekonomi dan Pendidikan Keluarga (Middle School Students Reading Interests: Factors of Economic Background and Family Education)

Abstract: This study aims to analyze students' reading interests based on economic background and family education. The population of this study was 203 students of SMP Negeri 3 Tarowang, Jeneponto, South Sulawesi. Data were collected through questionnaires and documentation. Data were analyzed by descriptive and inferential statistics. The results showed that (1) students' reading interests based on family economic background and family educational background were in the moderate category, (2) there were significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Perpustakaan di sekolah dan sumber bacaan di rumah perlu bertransformasi ke digital. Hal ini akan menjadi tantangan karena hasil riset Nurhaliza et al (2022) menunjukkan bahwa ada korelasi antara tingkat ekonomi dengan perilaku membaca peserta didik. Di satu sisi, faktor ekonomi dan pendidikan orang tua di Indonesia yang masih bervariasi sehingga kebutuhan membaca digital bisa jadi hanya akan terlayani bagi murid dengan ekonomi level menengah dan atas.…”
Section: Pembahasanunclassified
“…Perpustakaan di sekolah dan sumber bacaan di rumah perlu bertransformasi ke digital. Hal ini akan menjadi tantangan karena hasil riset Nurhaliza et al (2022) menunjukkan bahwa ada korelasi antara tingkat ekonomi dengan perilaku membaca peserta didik. Di satu sisi, faktor ekonomi dan pendidikan orang tua di Indonesia yang masih bervariasi sehingga kebutuhan membaca digital bisa jadi hanya akan terlayani bagi murid dengan ekonomi level menengah dan atas.…”
Section: Pembahasanunclassified
“…It needs a process and habituation that starts from how students do learning in class and how the teacher takes a position in learning, and trains them how to construct their own knowledge. Students should have enough freedom to develop themselves, explore the potential that exists within them so that they can develop according to the interests and talents that exist in these students (Hendy, 2020;Nurhaliza et al, 2022). The teacher is more in charge of facilitating the learning process, creating a good learning space and providing access to learning resources that are relevant to learning.…”
Section: Introductionmentioning
confidence: 99%
“…From the previous explanation, it can be concluded that digital-based media can be used as an innovation in increasing the resources of educators to be able to make diverse learning media innovations, especially in presenting fictional story material in improving speaking skills. For example in presenting fictional stories can also be made independently by educators so that the learning received by students can vary and add insight (Nurhaliza et al, 2022;Staley & Freeman, 2017). The first step for students in learning to think independently can be started with critical thinking in elementary school, while skills in reading and writing in Indonesia are still fairly low.…”
Section: Introductionmentioning
confidence: 99%